PROBLEMATIKA PELAKSANAAN KEKUASAAN KEHAKIMAN (Dalam Konteks Pelaksanaan Fungsi Check and Balances System) - Rumadan, Ismail (Jurnal Hukum dan Peradilan, 2014)
Efforts to support the creation of an independent judiciary as a constitutional mandate in itsÂ development has held several changes to the Judicial Authority Law, the last change is the Act Nomber 48 of 2009 on Judicial Authority. But these changes, when studied in depth is still set aside some very fundamental issues. The first is related to the function of law enforcement in the context of the criminal justice system. This concept requires that the law enforcement process should be integrated into a system of justice, but in fact the process of criminal justice, police and prosecutors are in a different scope of judicial power, so that the position can thus be ensured in the intervention process should be independent of law enforcement and free from any influence. The second problem is, of externally monitoring the functioning of the judicial power, which formally made by the Judicial Commission and the desired control by Parliament (as in the draft of the Supreme Court). Supervision models run by Judicial Commission nor desired by the House very serious effect on the performance of the functions of the judicial authorities even add complexity implementation of judicial power function itself, so that the implementation of judicial power considered not able to guarantee legal certainty and justice for litigants. This paper is limited to the study of these two issues in order to reinforce our commitment to build a sound administration of justice and independent in order to provide access to justice for all people and a healthy justice will only be realized in a reciprocal relationship between the environment and the environmental justice community. Keywords: The Judiciary, Law Enforcement